The inner cabinet: how mental health impacts political decision-making - James Weinberg; Ashley Weinberg (Parliamentary Affairs, 2026)
Abstract Politicians’ decisions have far-reaching societal impacts, but the mental health of representatives taking decisions remains overlooked. This article addresses this critical gap by theorizing and analyzing the link between common symptoms of poor mental health and political decision-making. Utilising data from two empirical studies involving 85 UK Members of Parliament (MPs) and a broader group of 128 international MPs, we demonstrate that poor mental health correlates with negative self-evaluations of decision-making, increased risk aversion, and heightened susceptibility to framing effects. Far from questioning the competence of those experiencing mental ill-health, these results highlight an urgent need for institutional reforms and support systems to improve job design, increase the sustainability of political careers, and assure the quality of political outcomes.